IMPLEMENTASI PERLINDUNGAN HUKUM TERHADAP PELAKU USAHA AKIBAT WANPRESTASI YANG DILAKUKAN KONSUMEN DALAM PEMBAYARAN HUTANG (STUDI KASUS DI UD. RUDI GROSIR DAN ECERAN, DESA PUHU) - Ariawan, Detha Djoni; Ardhya, Si Ngurah; Adnyani, Ni ketut sari (Universitas Pendidikan Ganesha, 2024)
This research aims to, (1) find out more about the implementation of legal protection for business actors due to default by consumers in paying debts at UD. Rudi Gosir and Puhu Village Retail, (2) to find out about the settlement stages of default actions carried out by consumers in paying debts at UD. Rudi wholesale and retail in Puhu village. This type of research uses empirical legal methods. The sample determination technique uses purposive sampling. The subjects of this research are consumers and business actors. Rudi wholesale and retail in Puhu village. The object of this research is legal protection for business actors due to default by consumers in paying debts, and the research location in this research is UD. Rudi wholesale and retail in Puhu village. The data collection techniques used in this research are document study, observation and interviews. The data collected was analyzed qualitatively. The results of this research show, (1) implementation of legal protection for business actors due to default by consumers in paying debts at ud. Wholesale and retail regulations have not been implemented optimally due to UD. Rudi wholesale and retail as business actors have not fully received their rights from consumers and their obligations based on statutory regulations have not been fully implemented by consumers. And this is also due to a lack of understanding regarding the regulations that cover this matter as well as consumers and business actors not yet fully understanding these regulations, (2) resolution of acts of default committed by consumers in paying debts at UD. Wholesale and retail sales are carried out in a non-litigation manner with the consideration of amicable negotiated settlements.